Thanksgiving at the Tappletons' - Spinelli, Eileen; Cocca-Leffler, Maryann, 1958- (New York : HarperCollins, 1992)
When calamity stalks every step of the preparations for the Tappletons' Thanksgiving dinner, they realize that there is more to Thanksgiving than turkey and trimmings.
"Ages 4-8"--Jacket.
Includes bibliographical references.
Booklist
Publisher's Weekly
Wilson's Children
4.3
Keywords: Thanksgiving Day -- Fiction; Thanksgiving Day -- Fiction